Histological studies on the development of Rat’s liver After Birth - Gheth, Ebtesam M. M.; Aboalhaj, Abdusalam M.; El-Gharbawy, Saad M. S.; El-Durssi, Ibrahim S.H. (Al-Mukhtar Journal of Sciences, 2008)
In this study, the development of the rat's liver was investigated after birth. using livers of 39 rats with ages from one day after birth to four months. The cells surround the central veins is not completely arranged and did not take their regular manner of arrangement till the 10th day after birth. At 10days of postnatal life the hepatic parenchyma was represented by regular hepatic cords some of them formed from one cell layer and the others were two cell layers thickness. These cords appeared in the form of radiating coulmns from the central veins. At 4 days of postnatal life the hepatic sinusoids became lined by Von kupffer cells beside the endothelial cells and at the 10th day after birth the hepatic sinusoids appeared more regular, extending between the hepatic cords and connected with the central veins. after birth the haemopiotic cells decreased in number and distribution. At age of 10 day after birth the hepatic lobules where clear containing central vein at the center and several portal areas at their angles. The capsule become more and more thick and the elastic fibers begin to appear in it at 10 day in postnatal life. After birth, reticular fibers increased in thickness and distribution, and collagen fibers appeared at the age of 10 days in the portal areas.